PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING (GBL) UNTUK MENINGKATKAN MINAT BELAJAR SISWA DI SMA NEGERI 1 LUBAI - Nurhayati, Nurhayati; Setyawati, Dewi; Wahyuni, Hikmah (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
This research is motivated by the researcher's desire to determine the Effect of the Game Based Learning Model (GBL) to Increase Student Interest in Learning at SMA 1 Lubai. The formulation of the problem is: 1) How is the process of implementing the Game Based Learning (GBL) learning model to increase interest in learning history of class X students of SMA Negeri 1 Lubai. 2) How are the learning outcomes of class X students after the Game Based Learning (GBL) learning model is applied at SMA Negeri 1 Lubai. 3) How is the effect of the Game Based Learning (GBL) learning model on the learning interest of class X students of SMA 1 Lubai. Method: Quasi experimental and survey method. Type of Research: Quantitative with an experimental design approach. Data Collection Techniques: observation, interviews, questionnaires, documentation, and evaluation results. Conclusion: 1) There is a process of implementing the Game Based Learning (GBL) learning model in history subjects for class X.1 (Experiment) with the material of Islamic Kingdoms in Indonesia (Kerajaan Samudra Pasai) carrying out several stages, namely: the preparation stage and the implementation stage. 2) After evaluating the significant results between classes X.1 (Experiment) and X.2 (Control) which can be seen from the results of the post-test, the highest score of 93 for class X.1 (Experiment) and the highest score of 75 for class X.2 (Control), it can be seen from the T test which shows that class X.1 (Experiment) and class X.2 (Control) have significant results <0.001 smaller than 0.05. Therefore, it can be stated that Ha is accepted and Ho is rejected and it can be stated that there is an influence after implementing the Game Based Learning (GBL) learning model on the learning outcomes of class X students of SMA 1 Lubai. 3) The influence of the Game Based Learning (GBL) learning model on learning interest has a significant influence between class X.1 (Experiment) using the Game Based Learning (GBL) method and X.2 (Control) using the lecture and question and answer method, it can be seen from the results of the T test which shows that there is a difference between class X.1 (experiment) and X.2 (Control) which has a significant 0.003 less than 0.05. meaning Ha is accepted and Ho is rejected, so it can be concluded that there is an influence of the Game Based Learning (GBL) learning model on history subjects in increasing students' learning interest.